PLASTIC BEARING CAPACITY OF THE STEEL ELEMENT CROSS-SECTION BY INTERNAL FORCES COMBINATION AND RESTRAINT - Hudz, Serhii; Gasii, Grygorii; Нasenko Anton; Dariienko, Viktor (Academic journal Industrial Machine Building Civil Engineering, 2019)
The article examines the features of determining the bearing capacity of the steel profile cross-section, rolled or composed from three sheets with arbitrary thickness, considering the development of plastic deformations in a complex combination of different power factors that may occur during spatial loss of stability. Based on a new approach to the perception character of internal forces, the goal is to investigate their ability to redistribute between separate linear elements, on which cross-section of the beam is broken. It is proposed to increase the savings of the material by detailing the calculation.